2009
DOI: 10.4102/sajpsychiatry.v15i1.99
|View full text |Cite
|
Sign up to set email alerts
|

Cannabis use and abuse correlates in a homogenous South African schizophrenia population

Abstract: <p><strong>Objective.</strong> Worldwide, cannabis is the most widely used illicit substance, and it has been identified as a correlate in schizophrenia samples for poorer symptomatic and functional outcomes in many international studies. The object of this retrospective study was to identify the prevalence of cannabis use/abuse and the demographic and clinical correlates therefor in a large homogeneous South African schizophrenia population.</p><p><strong>Methods.</stron… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
7
1

Year Published

2011
2011
2022
2022

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(9 citation statements)
references
References 28 publications
1
7
1
Order By: Relevance
“…13 In contrast to previous studies 1,6,14,15 , we found a significant association between cannabis use and shorter DUP and a trend association between the use of cannabis and a relative absence of negative symptoms. Also, unlike these studies, we did not find increased positive symptoms, nor was there any association with AO (a finding that has been reported from both developed and developing countries [3][4][5][12][13][14][15] ). Clearly then the relationship between cannabis use and onset of FEP is complex.…”
Section: Discussioncontrasting
confidence: 94%
See 3 more Smart Citations
“…13 In contrast to previous studies 1,6,14,15 , we found a significant association between cannabis use and shorter DUP and a trend association between the use of cannabis and a relative absence of negative symptoms. Also, unlike these studies, we did not find increased positive symptoms, nor was there any association with AO (a finding that has been reported from both developed and developing countries [3][4][5][12][13][14][15] ). Clearly then the relationship between cannabis use and onset of FEP is complex.…”
Section: Discussioncontrasting
confidence: 94%
“…The ethnic distribution of our sample was consistent with that of the local population while the prevalence of cannabis use/abuse (35%) approximated that reported in other African studies: 38% in the Gambia 12 and 35-49% in South Africa. 3,13 The slight gender bias in prevalence of cannabis use observed in our study (37% of males and 28% of females) was also similar to that reported by Roos and colleagues. 13 In contrast to previous studies 1,6,14,15 , we found a significant association between cannabis use and shorter DUP and a trend association between the use of cannabis and a relative absence of negative symptoms.…”
Section: Discussionsupporting
confidence: 91%
See 2 more Smart Citations
“…Objective 6: Intersectoral collaboration (Table 6) • Examples of cases in psychiatry where intersectoral collaboration is central include: community-based residential and psycho-social rehabilitation facilities and services; forensic psychiatry; substance abuse and addiction; [31,32] child and adolescent psychiatry, and geriatric psychiatry. [33] Objective 7: Human resources for mental health (Table 7) • …”
Section: • Forensic Services Must Be Reviewed Preferably Through An mentioning
confidence: 99%